ANALISIS KEBIJAKAN PENDIDIKAN KELUARGA DALAM MEMANTAPKAN PERILAKU MORAL ANAK DI KABUPATEN ACEH TENGAH - Wen Yusri Rahman; Murniati AR; Djailani AR (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2015)
Abstract: Children’s moral behavior is influenced by formal and non-formal education. The system of education is also influenced by educational policy. Formulation, implementation of educational policy needs to be evaluated for being appropriate to the objective of education. This research aimed to find out the implementation of educational policy, which included: 1) Program of family education, 2) Implementation of educational policy, and 3) Educational obstacles for improving children’s moral behavior in Aceh Tengah District. The research used a descriptive method with a qualitative approach. Data collection techniques were conducted through interview, documentation and observation. The subjects of research were Head of Education Ministry in Aceh Tengah District and society figure. From the research results, it was found that there was no one of government policy which was established into regional government regulations (qanun) about children’s moral education, and many family education programs were still run based on parents experience by generation to generation. For children’s moral education out of school time, a regional government issued appeals of reading Al Quran after magrib and activating communal Quran reading. The obstacles of family education in Aceh Tengah were that unequal parental education and weak economy so that children’s development was given over to education institutions. There were no programmed, detailed socialization and society mapping,and the role of society in educating a generation had already been decreased since it was oriented materials. It is recommended that a program of family education about children’s moral should be formulated to be a regional policy by involving all stakeholders. Keywords: Educational policy and family education Abstrak: Perilaku moral anak dipengaruhi oleh pendidikan formal dan non formal. Sistem pendidikan juga dipengaruhi oleh kebijakan pendidikan. Perumusan, implementasi kebijakan pendidikan perlu dievaluasi agar sesuai dengan tujuan pendidikan. Penelitian ini bertujuan untuk mengetahui pelaksanaan kebijakan pendidikan keluarga dalam memantapkan perilaku anak di Kabupaten Aceh Tengah, mencakup, 1) Program pendidikan keluarga, 2) Pelaksanaan kebijakan pendidikan, dan 3) Hambatan-hambatan pendidikan dalam memantapkan prilaku moral anak di Kabupaten Aceh Tengah. Penelitian menggunakan metode deskriptif dengan pendekatan kualitatif, sedangkan tekhnik pengumpulan data melalui wawancara, dokumentasi dan observasi. Subjek penelitiannya adalah Kepala Dinas Pendidikan Kabupaten Aceh Tengah dan tokoh masyarakat. Hasil penelitian, ditemukan belum adanya satupun kebijakan pemerintah yang ditetapkan ke dalam peraturan pemerintah daerah (qanun) untuk pendidikan moral anak, program pendidikan keluarga masih banyak dijalankan berdasarkan pengalaman orang tua secara turun temurun. Pendidikan moral anak di luar jam sekolah, pemerintah daerah mengeluarkan himbauan mengaji ba’da magrib dan mengaktifkan pengajian-pengajian. Hambatan pendidikan keluarga di Aceh Tengah yaitu tidak meratanya pendidikan orang tua, ekonomi lemah, sehingga perkembangan anak diserahkan kepada lembaga pendidikan. Sosialisasi dan pemetaan masyarakat yang rinci dan terprogram belum ada, peran masyarakat dalam mendidik generasi sudah mulai berkurang karena berorientasi pada materi. Perlu direkomendasikan, program pendidikan keluarga tentang moral anak harus dirumuskan menjadi kebijakan daerah dengan melibatkan seluruh stakeholder. Kata Kunci: Pendidikan keluarga dan kebijakan pendidikan